Nano Devices and Circuit Techniques for Low-Energy Applications and Energy Harvesting - Kyung, Chong-Min (KAIST Research Series,, 2016)
This book describes the development of core technologies to address two of the most challenging issues in research for future IT platform development, namely innovative device design and reduction of energy consumption. Three key devices, the FinFET, the TunnelFET, and the electromechanical nanoswitch are described with extensive details of use for practical applications. Energy issues are also covered in a tutorial fashion from material physics, through device technology, to innovative circuit design. The strength of this book lies in its holistic approach dealing with material trends, state-of-the-art of key devices, new examples of circuits and systems applications.    This is the first of three books based on the Integrated Smart Sensors research project, which describe the development of innovative devices, circuits, and system-level enabling technologies.  The aim of the project was to develop common platforms on which various devices and sensors can be loaded, and to create systems offering significant improvements in information processing speed, energy usage, and size. The book contains extensive reference lists and with over 200 figures  introduces the reader to the general subject in a tutorial style, also addressing the state-of-the-art,  allowing it to be used as a guide for starting researchers in these fields.  .